Modernizing Local Tax Policy: The Role of Digitalization in Land and Building Tax Administration - Mandiri, Prabu; Alfitri, Alfitri; Thamrin, M. Husni; Najib, Abdul (Journal Public Policy, 2024)
The objective of this research is to identify and analyze the impact of digitalizing the Land and Building Tax Stimulus Policy on the primary issue, namely public compliance and the overall potential. This study adopts a qualitative research approach, with case study method. The research reveals that, The digital transformation of Land and Building Tax (Pajak Bumi dan Bangunan, PBB) administration in Palembang signifies a monumental step towards modernizing local tax policies. This study highlights key findings that underscore the effectiveness of digitalization in enhancing the efficiency, accuracy, transparency, and overall revenue collection of local governments. The evidence illustrates that the integration of digital systems not only streamlines administrative processes but also minimizes errors and accelerates payment cycles, that can ultimately leading to higher compliance rates among taxpayers. Altough in there is still an obstecles in the process, but the overall potential can bring apositive impact on PAD